Educational Study in A Methodological Perspective of the Thinking of Abdurrahman Wahid and Nurcholis Madjid - Abdullah Muwaffaq (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
The rise of truth claims, radicalism, politicization, and religious fundamentalism, as well as discourses on the formalization of the khilāfah al-Islamiyah state's sharia, have caused divisions and threatened the stability of the Indonesian state. One of these problems is motivated by the learning of Islamic Religious Education (PAI) which is doctrinal, exclusive, and normative. Therefore, an alternative solution is needed through multicultural, inclusive, and pluralist Islamic Religious Education Learning based on the Islamic spirit by grounding Islam rahmatan lil 'ālamīn and an Indonesian spirit that respects diversity (plurality). There are two Indonesian Muslim thinkers and intellectuals who actively voice the spirit of Islam and Indonesianness, namely Abdurrahman Wahid and Nurcholish Madjid. The purpose of this research is to understand Abdurrahman Wahid and Nurcholish Madjid's thoughts on educational studies from a methodological perspective. Regarding the concept of Islamic and Indonesian-ness spirit and its contribution to the development of Islamic Religious Education. The results of the study show that the great contribution of Abdurrahman Wahid and Nurcholish Madjid's thoughts regarding the spirit of Islam and Indonesianness to the Development of Islamic Religious Education is the realization of the renewal of Islamic education that is humane, egalitarian, democratic, and inclusive-plural.